Analisis Pengaruh Kedisiplinan Kerja, Keselamatan dan Kesehatan Kerja (K3), Serta Lingkungan Kerja Terhadap Kinerja Karyawan PT. BBIC BERCA CABLES di Kabupaten Tangerang - Nurdin, Muhamad Ali; Erislan, Erislan; Ramli, Soehatman (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
PT. BIIC Berca Cables is a company that produces electrical cables and fiber optic cables. Supervising employee discipline, safety & health and the work environment is a way to maintain or improve employee performance. In the preliminary survey conducted, it showed that employee performance was considered to have not met the company's expectations, where many failures were still found during the Optic Cable Quality Test process. The aim of this research is to partially analyze (1) the influence of work discipline variables, (2) occupational safety and health (OSH), and (3) the work environment on employee performance and simultaneously analyze the influence of work discipline, occupational safety and occupational health (OSH) as well as the work environment on employee performance. The research design is associative quantitative, which is a depiction of the relationship between one variable and another. Researchers distributed questionnaires to employees as a method of data collection techniques. The analysis technique used is Correlation Test, Multiple Linear Regression Analysis. In the classical assumption test there is a normality test, multicollinearity test and heteroscedasticity test. From the research results it can be concluded that partially the work discipline variable has a significant positive effect on employee performance, the occupational safety and health (OSH) variable has a significant positive effect, and the work environment variable has a significant positive effect. Simultaneously, work discipline variables, occupational safety and health (K3) variables, and work environment variables have a positive and significant effect on the performance of PT employees. BIIC Berca Cables in Tangerang Regency. Keywords : Discipline, Safety, Health, Environment, Employee Performance